IL-12 DNA Displays Efficient Adjuvant Effects Improving Immunogenicity of Ag85A in DNA Prime/MVA Boost Immunizations - Morelli, María Paula; Del Medico Zajac, María Paula; Pellegrini, Joaquín Miguel; Amiano, Nicolás Oscar; Tateosian, Nancy Liliana; Calamante, Gabriela; Gherardi, María Magdalena; García, Verónica Edith (Frontiers in Cellular and Infection Microbiology, 2020)
Mycobacterium tuberculosis (Mtb) infection is one of the leading causes of death worldwide. The Modified Vaccinia Ankara (MVA) vaccine vector expressing the mycobacterial antigen 85A (MVA85A) was demonstrated to be safe, although it did not improve BCG efficacy, denoting the need to search for improved tuberculosis vaccines. In this work, we investigated the effect of IL-12 DNA -as an adjuvant- on an Ag85A DNA prime/MVA85A boost vaccination regimen. We evaluated the immune response profile elicited in mice and the protection conferred against intratracheal Mtb H37Rv challenge. We observed that the immunization scheme including DNA-A85A+DNA-IL-12/MVA85A induced a strong IFN-γ production to Ag85A in vitro, with a significant expansion of IFN-γ+CD4+ and IFN-γ+CD8+ anti-Ag85A lymphocytes. Furthermore, we also detected a significant increase in the proportion of specific CD8+CD107+ T cells against Ag85A. Additionally, inclusion of IL-12 DNA in the DNA-A85A/MVA85A vaccine scheme induced a marked augment in anti-Ag85A IgG levels. Interestingly, after 30 days of infection with Mtb H37Rv, DNA-A85A+DNA-IL-12/MVA85A vaccinated mice displayed a significant reduction in lung bacterial burden. Together, our findings suggest that IL-12 DNA might be useful as a molecular adjuvant in an Ag85A DNA/MVA prime-boost vaccine against Mtb infection.